2019
DOI: 10.2298/fil1902449c
|View full text |Cite
|
Sign up to set email alerts
|

A note on the spectrum of discrete Klein-Gordon s-wave equation with eigenparameter dependent boundary condition

Abstract: This paper is concerned with the boundary value problem (BVP) for the discrete Klein-Gordon equation a n−1 y n−1 + (v n − λ) 2 y n = 0, n ∈ N and the boundary condition γ 0 + γ 1 λ y 1 + β 0 + β 1 λ y 0 = 0 where (a n) , (v n) are complex sequences, γ i , β i ∈ C, i = 0, 1 and λ is a eigenparameter. The paper presents Jost solution, eigenvalues, spectral singularities and states some theorems concerning quantitative properties of the spectrum of this BVP under the condition n∈N exp n δ (|1 − a n | + |v n |) < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…He also showed that these eigenvalues and spectral singularities are of finite number with finite multiplicities under certain conditions. Later developments in this area concerned spectral analysis of the boundary value problems of the differential and discrete operators including Sturm-Liouville, Klein-Gordon, quadratic pencils of Schrödinger and Dirac-type operators within the context of determination of Jost solution and providing suffcient conditions guaranteeing the finiteness of the eigenvalues and spectral singularities [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also showed that these eigenvalues and spectral singularities are of finite number with finite multiplicities under certain conditions. Later developments in this area concerned spectral analysis of the boundary value problems of the differential and discrete operators including Sturm-Liouville, Klein-Gordon, quadratic pencils of Schrödinger and Dirac-type operators within the context of determination of Jost solution and providing suffcient conditions guaranteeing the finiteness of the eigenvalues and spectral singularities [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Note that investigation of discrete analogues of ordinary differential operators is an important research area since difference equtions are well suited to find solutions with the aid of computers and can model many contemporary problems arising in control theory, biology, and engineering [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%